Settled knowledge practices, truncated imaginations. (March 2023) - Vijay, Devi
Martin Parker recently auto-critiqued his book Against Management . Parker reflected on the book's circulation, responded to some criticisms, and proposed a manifesto for a School of Organizing that must emphasize alternative organizational forms. I highlight the Eurocentric frame that permeates the book and the auto-critique. This Eurocentrism manifests as settled geographies, histories, and epistemic practices. Such knowledge practices truncate the possibilities of radically imagining alternatives to the contemporary crises of capitalism. I borrow Anna Lowenhaupt Tsing's metaphor of foraging to briefly consider how subterranean struggles and solidaristic transgressions offer possibilities for alternative world-making.